The essential role of large research vessels in marine ecosystem observations and ocean sustainability - Erin V. Satterthwaite; John C. Field; Andrea J. Fassbender; Gerardo Aceves‐Medina; Steven J. Bograd; Elliott L. Hazen; Nastassia V. Patin; Zachary Gold; Katherine A. Barbeau; Danie Kinkade; Adam Shepherd; Rasmus Swalethorp; et al. (Limnology and Oceanography, 2025)
Our understanding of marine ecosystems and ability to manage them sustainably has come from multidisciplinary observations made repeatedly over long periods of time. These long‐term ecosystem observations depend on the capabilities of large research vessels, which play an essential role in the collection of global ocean observations. Research vessels serve as large, stable platforms for collecting high volume samples from the surface to the seafloor that provide uniquely valuable in situ marine ecosystem information. Additionally, they serve as mobile laboratories enabling the collection, preservation, processing, and analysis of unique samples and data, such as chemical, biogeochemical, and biological parameters. Given their capacity for, and repeated use in, collecting comprehensive marine ecosystem observations—across geology, physics, chemistry, and biology—large research vessels provide insight into long‐term regional ecosystem dynamics. They also act as platforms‐of‐opportunity for testing, refining, and comparing technologies, enabling innovation and the evolution of the observing system. High‐quality observations from large research vessels serve as the backbone for many other components of the global ocean observing system through their use in calibrating autonomous sensors and predictive modeling. Moreover, large research vessels function as mobile, experiential training and exploration platforms that facilitate discovery, education, and collaboration. An effective, modular marine ecosystem observing system will depend on large research vessels to sustain and augment existing observing programs and to deploy, service, and validate the growing array of autonomous platforms that contribute to it. Achieving this vision will likely require maintaining and upgrading ship‐based infrastructure and personnel, integrating emerging technologies, leveraging the unique capabilities of large research vessels in conjunction with other platforms, strengthening collaborative partnerships, and building social capital for marine ecosystem observations through training, knowledge sharing, and effective governance.